2012
DOI: 10.1101/gr.129544.111
|View full text |Cite
|
Sign up to set email alerts
|

After the bottleneck: Genome-wide diversification of the Mycobacterium tuberculosis complex by mutation, recombination, and natural selection

Abstract: Many of the most virulent bacterial pathogens show low genetic diversity and sexual isolation. Accordingly, Mycobacterium tuberculosis, the deadliest human pathogen, is thought to be clonal and evolve by genetic drift. Yet, its genome shows few of the concomitant signs of genome degradation. We analyzed 24 genomes and found an excess of genetic diversity in regions encoding key adaptive functions including the type VII secretion system and the ancient horizontally transferred virulence-related regions. Four di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
128
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 135 publications
8
128
3
Order By: Relevance
“…In contrast, a recent study has reported homoplastic SNP regions with at least two nucleotides concerned, present in different strains of the M. tuberculosis complex, suggesting that potential recombination tracts of small sizes might exist within their genomes (88). However, three of the four examples of suggested recombination tracts presented (in Fig.…”
Section: Microevolutionary Genomics Of the Tubercle Bacillimentioning
confidence: 43%
See 1 more Smart Citation
“…In contrast, a recent study has reported homoplastic SNP regions with at least two nucleotides concerned, present in different strains of the M. tuberculosis complex, suggesting that potential recombination tracts of small sizes might exist within their genomes (88). However, three of the four examples of suggested recombination tracts presented (in Fig.…”
Section: Microevolutionary Genomics Of the Tubercle Bacillimentioning
confidence: 43%
“…However, three of the four examples of suggested recombination tracts presented (in Fig. S4 of reference 88), correspond to adjacent base pairs changes, i.e., putative tandem-base mutations, shared by strains within particular subclusters of M. tuberculosis lineages (88). While these tandem-base mutations seem perfectly compatible with a strictly clonal evolution scenario, the remaining example of a SNP signature shared among M. africanum CPHL_A and the M. tuberculosis CDC1551-and C-strains might more likely be the result of a recombination event (88).…”
Section: Microevolutionary Genomics Of the Tubercle Bacillimentioning
confidence: 99%
“…Whereas the M. canettii strain-specific genes might be the result of recent HGT among these strains and other environmental bacteria, the supposed transfer of pe_pgrs33 to the common ancestor of the MTBC might represent a more ancient occurrence, at the beginning of the clonal emergence of the MTBC from M. canettii-like generalist bacteria toward pathogens of mammalian hosts. However, unlike previously postulated (8,9), the ability of extensive HGT seems to have been lost during the development of this lineage into the extant MTBC, as is suggested by the here-reported failure of obtaining recombinants among different M. tuberculosis strains despite extensive attempts, and the observed clonal strain cluster organization within lineage 1-7 strains (Fig. 2).…”
mentioning
confidence: 61%
“…However, the contribution of HGT to the (recent) evolution of mycobacteria and the impact on the most dominant pathogenic species, Mycobacterium tuberculosis, the agent of human tuberculosis, remains controversial. Several studies provide overall congruence that the classical M. tuberculosis complex (MTBC) shows a perfectly clonal population structure (1-7), yet, other studies have proposed that frequent genetic exchange among MTBC strains might exist (8,9). As potential interstrain recombination in tubercle bacilli influences the risk evaluation for transfer of drug resistance-associated mutations between clinical M. tuberculosis isolates, novel insights into the question of HGT among tubercle bacilli are of utmost importance.…”
mentioning
confidence: 99%
“…SNP phylogenetic informativeness MTBC species provide a good example of clonal evolution (Smith et al, 2003). In fact, up until recently there was almost no evidence of recombination of these species (Liu et al, 2006;Namouchi et al, 2012). Because of this, in general, the emergence of a particular polymorphism in MTBC species can be mapped as a single event in a phylogenetic tree.…”
Section: Strain Identification By Co-clusteringmentioning
confidence: 99%